PERENCANAAN PAJAK DALAM UPAYA PENGHEMATAN PAJAK PENGHASILAN KLINIK ABC DI SURABAYA - Betsy Ardelia Sony (Behavioral Accounting Journal, 2020)
Development of a business is also followed by increasing profits. Every profit earned by a company potentially subject to income tax. Some entrepreneurs feel that income tax is an additional cost for businesses so that there are some companies do tax planning. One of the businesses that developed quite rapidly in the last years is the beauty industries. For this reason, the object of this research comes from the beauty business industry, which is an aesthetic clinic. The purpose of this qualitative research is to provide appropriate tax planning recommendations for ABC Clinic’s businesses in Surabaya. Method that used in this research are interview, observation, and document analisys. After all analisys and calculation done during this research, a tax planning that fit to ABC Clinic business characteristics are use appropriate tax rates, minimizing fiscal correction, business segregtion, and avoiding tax audit. This tax plannng strategy can provide income tax savings up to 50% for the company.